2006
DOI: 10.1177/1075547006293916
|View full text |Cite
|
Sign up to set email alerts
|

Seeking and Processing Information about Impersonal Risk

Abstract: Attempts to model risk response tend to focus on risks that pose a direct personal threat. This study examined the applicability of one risk response model to impersonal risks-risks that threaten something other than the self, in this case, the environment. This study utilized a section of the Griffin et al. riskinformation seeking and processing model, which depicts relationships between informational subjective norms and information seeking and processing as being mediated by perceptions of information insuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
212
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 188 publications
(241 citation statements)
references
References 58 publications
17
212
1
2
Order By: Relevance
“…The RISP model depicts this cognitive need for information sufficiency as the key motive for information seeking. Past research has also found that perceived information sufficiency could lead to information-avoidance (Kahlor, Dunwoody, Griffin, & Neuwirth, 2006). That is, when people are satisfied with the amount of information they already have about a specific risk, they are likely to avoid further information on this topic.…”
Section: Risk Information-seeking and Processing Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…The RISP model depicts this cognitive need for information sufficiency as the key motive for information seeking. Past research has also found that perceived information sufficiency could lead to information-avoidance (Kahlor, Dunwoody, Griffin, & Neuwirth, 2006). That is, when people are satisfied with the amount of information they already have about a specific risk, they are likely to avoid further information on this topic.…”
Section: Risk Information-seeking and Processing Modelmentioning
confidence: 99%
“…In the RISP model, perceived information-gathering capacity mainly deals with one's ability to access and understand risk information. Several RISP studies have found a positive relationship between this concept and current knowledge about a risk issue (Griffin et al, 2008;Kahlor et al, 2006;ter Huurne et al, 2009). …”
Section: Risk Information-seeking and Processing Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…risks that are a direct threat to something other than the self, instead of a personal risk. Previous research (Kahlor, Dunwoody, Griffin & Neuwirth, 2006) showed that social norms were most important in predicting information seeking and processing in relation to impersonal risks, while other relations were less prominent. This might explain our low effect of risk perception and anxiety and the strong effect of social norms.…”
Section: Discussion Of Empirical Resultsmentioning
confidence: 99%